2019
DOI: 10.14254/2071-8330.2019/12-3/3
|View full text |Cite
|
Sign up to set email alerts
|

Financial performance of microfinance institutions in Kosovo

Abstract: This article seeks to investigate the determinants of financial performance of microfinance institutions in Kosovo over the period of 2007-2016. The data has been taken from twelve microfinance institutions in Kosovo. The dependent variables used as proxies for microfinance institutions' (MFI) performance are Operational self-sufficiency (OSS), Return on Assets (ROA) and Profit Margin (PM). ROA and PM are widely used indicators to analyse financial performance or profitability of MFI. The findings of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Microfinance as a financial service provides access to financial services for low-income and unemployed people. It has been quite successful in reducing poverty and promoting economic development (Shkodra, 2019). This is also argued in (Fidrmuc & Kostagianni, 2015) who found that allowing for the IMF assistance to affect growth with a lag is enough to obtain a positive impact on growth.…”
Section: Introductionmentioning
confidence: 89%
“…Microfinance as a financial service provides access to financial services for low-income and unemployed people. It has been quite successful in reducing poverty and promoting economic development (Shkodra, 2019). This is also argued in (Fidrmuc & Kostagianni, 2015) who found that allowing for the IMF assistance to affect growth with a lag is enough to obtain a positive impact on growth.…”
Section: Introductionmentioning
confidence: 89%
“…Kosovo has capacity in having advantages in various agricultural sectors (fruits and vegetables), yet needs to exceed many challenges and difficulties, mostly owing to the poor production and competitive capacity (Beluhova-Uzunova & Lubeniqi, 2019). Some of the difficulties confronted by Kosovo's farmers are lack of coordination, low level of education and training (KAS, 2014), advisory service, poor knowledge in the usage of technology, high interest rate on loans (Shkodra, 2019), insufficient experience, low technical efficiency, limited market access, and particularly, trade barriers from neighbor countries. The main concern is low level of cooperation between farmers due to the lack of trust in the cooperative institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the more recent studies, derived similar conclusions. Study conducted by Shkodra (2019) showed that for MFIs located in Kosovo, size, year, inflation, and GDP have important influence on their financial performance. Study also implies that among most significant coefficients, to reflect financial performance is certainly gross portfolio yield which is revealed as positively significant across all three financial performance indicators, namely OSS, Return on Assets (ROA) and Profit Margin (PM).…”
Section: Literature Reviewmentioning
confidence: 99%